2022
DOI: 10.3390/foods11203281
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Exergetic, Energetic and Techno-Economic Analyses on a Gas-Type Industrial Drying System of Black Tea

Abstract: The purpose of this research work is to perform detailed exergetic, energetic and techno-economic analysis of the black tea drying process in the gas-type industrial dryer. Exergy–energy and techno-economic methodology was applied to investigate the heat loss, exergetic and energetic performance, exergy efficiency, improvement potential rate, sustainability index and techno-economic performance of a drying system. The results showed that the heat loss of exhaust air in the late drying process played a main con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…However, the high-salt environment possesses oxidative properties that accelerate lipid oxidation in aquatic products, resulting in the generation of a significant amount of cholesterol oxidation products. This, in turn, affects the oxidative stability of aquatic products, leading to a decline in product quality and a shortened shelf life [13][14][15][16][17][18][19][20]. In a study by Yu et al [21], using Pacific saury as the material, changes in the physicochemical characteristics during the salting process were analyzed and determined.…”
Section: Traditional Preprocessing Techniquesmentioning
confidence: 99%
“…However, the high-salt environment possesses oxidative properties that accelerate lipid oxidation in aquatic products, resulting in the generation of a significant amount of cholesterol oxidation products. This, in turn, affects the oxidative stability of aquatic products, leading to a decline in product quality and a shortened shelf life [13][14][15][16][17][18][19][20]. In a study by Yu et al [21], using Pacific saury as the material, changes in the physicochemical characteristics during the salting process were analyzed and determined.…”
Section: Traditional Preprocessing Techniquesmentioning
confidence: 99%
“…The authors emphasized the potential of exergy analysis in reducing energy consumption in similar processes. Zeng et al (2022) applied an energy and exergy method to evaluate the energetic and exergetic performance of a gas-type industrial drying system of black tea. They found that the exhaust air heat loss had a major synergetic role in the exergy loss of the whole dryer unit.…”
Section: Introductionmentioning
confidence: 99%
“…Lin, J et al [23] studied the gas-solid coupling of an aggregate gas dryer by using the computational fluid dynamics-discrete element method (CFD-DEM) coupling method, which effectively improved the heat exchange efficiency between flue gas and aggregate. Zeng, Z et al [24] analyzed the exergy performance, energy, and technical economy of the gas dryer, and the research results showed that the loss of high-temperature flue gas generated by gas combustion restricted the drying efficiency of the gas dryer.…”
Section: Introductionmentioning
confidence: 99%